PEMBANGUNAN EKOSISTEM DIGITAL UNTUK MENINGKATKAN PELAYANAN PUBLIK DI DESA LAMAHU KECAMATAN BULANGO SELATAN PROVINSI GORONTALO - Tirza Haqia Purnama; Roni Ekha Putera; Tengku Rika Valentina (LPPM Universitas Andalas, 2024)
The development gap between urban and rural areas has triggered the birth of the digital village program. The purpose of this service is to rebuild the digital ecosystem in Lamahu Village through various innovations that support village digitalization and improve access to information. The methods used include observation, interviews, village needs analysis, and technology usage training. This activity lasted for four months, focusing on the development and implementation of relevant technological solutions for the village community. During this service, five main projects were successfully developed: (1) The web-based application DIGICORE LAMAHU to enhance information access and facilitate various services in the village, (2) The Lamahu village map as a means of providing information on the village's territory and infrastructure, (3) A village profile video as a promotional medium for the village's potential, (4) A policy brief providing policy recommendations to the village government, and (5) Digitalization training for SMEs to support the development of micro, small, and medium enterprises in the village. This service ran well and produced various beneficial products. Direct interaction with the Lamahu Village community broadened insights into local social and economic realities. The sustainability of this program requires ongoing support from the local government and capacity building through advanced training. Active participation of the community is also crucial for the success and sustainability of this program. The project's results are expected to facilitate public services in Lamahu Village and serve as a model for the digitalization of other villages in Gorontalo Province and Indonesia.